A stratigraphic investigation of the Celtic Sea megaridges based on seismic and core data from the Irish-UK sectors. (15th October 2018) - Lockhart, Edward A.; Scourse, James D.; Praeg, Daniel; Van Landeghem, Katrien J.J.; Mellett, Claire; Saher, Margot; Callard, Louise; Chiverrell, Richard C.; Benetti, Sara; Cofaigh, Colm Ó.; Clark, Chris D.
Abstract: The Celtic Sea contains the world's largest continental shelf sediment ridges. These megaridges were initially interpreted as tidal features formed during post-glacial marine transgression, but glacigenic sediments have been recovered from their flanks. We examine the stratigraphy of the megaridges using new decimetric-resolution geophysical data correlated to sediment cores to test hypothetical tidal vs glacial modes of formation. The megaridges comprise three main units, 1) a superficial fining-upward drape that extends across the shelf above an unconformity. Underlying this drape is 2), the Melville Formation (MFm) which comprises the upper bulk of the megaridges, sometimes displaying dipping internal acoustic reflections and consisting of medium to coarse sand and shell fragments; characteristics consistent with either a tidal or glacifluvial origin. The MFm unconformably overlies 3), the Upper Little Sole Formation (ULSFm), previously interpreted to be of late Pliocene to early Pleistocene age, but here shown to correlate to Late Pleistocene glacigenic sediments forming a precursor topography. The superficial drape is interpreted as a product of prolonged wave energy as tidal currents diminished during the final stages of post-glacial marine transgression. We argue that the stratigraphy constrains the age of the MFm to between 24.3 and 14 ka BP, based on published dates, coeval with deglaciation and a modelled period of megatidal conditions during post-glacial marine transgression. Stratigraphically and sedimentologically, the megaridges could represent preserved glacifluvial features, but we suggest that they comprise post-glacial tidal deposits (MFm) mantling a partially-eroded glacial topography (ULSFm). The observed stratigraphy suggests that ice extended to the continental shelf-edge. Highlights: The megaridges mainly comprise an upper sand unit mantling a precursor topography. The underlying topography is of glacial origin, having survived an erosion event. The megaridges may represent tidal deposits overlying a preserved glacial topography.